Infographic-assisted four-square writing strategy in narrative text writing instruction for senior high school students - Sitti Aisyah; Waliyudin Waliyudin; Nashruddin Nashruddin (Journal of English Language Teaching, Literatures, Applied Linguistic (JELTLAL), 2026)
This study aims to examine the effectiveness of the infographic-assisted four-square writing strategy in teaching narrative text writing. Research method was a quasi-experimental design using a non-equivalent control group design. From 160 students of X-class at SMA Dirgantara, 64 students were selected as research sample using a purposive sampling technique. Data were collected through writing ability test and observation, then analyzed using normality, homogeneity, N-Gain, and t-tests. From data analysis results, the experimental group demonstrated a significantly greater improvement than the control group, as indicated by an independent-samples t-test on the gain scores (p < 0.05) with a large effect size (0.790). Furthermore, the experimental group achieved a higher normalized gain (N-Gain = 59,96), compared with the control group (N-Gain = 38,01). These results show an improvement in writing ability in both the control and experimental classes, but the latter experienced a greater improvement. Hypothesis test shows a significant difference between the two groups. The integration of infographic media with the four-square writing strategy, which offers a structured and visually supported approach to enhance students’ narrative writing skills, shows the novelty of this study. The findings contribute to the development of more innovative and visual media-based writing instruction strategies in language classrooms. Consequently, as the practical implication, teachers can integrate this strategy to enhance the quality of the process and students’ learning outcomes in writing narrative texts.